2021
DOI: 10.1016/j.fmre.2021.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Immune responses to SARS-CoV-2 infection in Humans and ACE2 humanized mice

Abstract: The coronavirus disease 2019 (COVID-19) pandemic caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) represents a major public health threat worldwide. Insight into protective and pathogenic aspects of SARS-CoV-2 immune responses is critical to work out effective therapeutics and develop vaccines for controlling the disease. Here, we review the present literature describing the innate and adaptive immune responses including innate immune cells, cytokine responses, antibody responses and T ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 80 publications
1
4
0
Order By: Relevance
“…In our system, rapid replication of SARS-CoV-2 in the early stage of infection induces acute inflammation, including elevated cytokines and chemokines, and contributes to lung lesions and lethality, which is in agreement with the report described in COVID-19 patients (40). Furthermore, FACS analyses revealed that the neutrophil count was elevated and lymphopenia-like symptoms were observed in infected CAG-hACE2 mice during the late stage of infection, when the histological scores were high (Supplemental Figs 4-7 and Figure 3B), which was consistent with the findings in severe COVID-19 patients (41). These results suggest that the infection model of CAG-hACE2 mice developed acute severe lung injury accompanied with elevated pro-inflammatory cytokines and chemokines; therefore, CAG-hACE2 mice provide the possibility for evaluation of medical arms for ARDS with COVID-19.…”
Section: Discussionsupporting
confidence: 91%
“…In our system, rapid replication of SARS-CoV-2 in the early stage of infection induces acute inflammation, including elevated cytokines and chemokines, and contributes to lung lesions and lethality, which is in agreement with the report described in COVID-19 patients (40). Furthermore, FACS analyses revealed that the neutrophil count was elevated and lymphopenia-like symptoms were observed in infected CAG-hACE2 mice during the late stage of infection, when the histological scores were high (Supplemental Figs 4-7 and Figure 3B), which was consistent with the findings in severe COVID-19 patients (41). These results suggest that the infection model of CAG-hACE2 mice developed acute severe lung injury accompanied with elevated pro-inflammatory cytokines and chemokines; therefore, CAG-hACE2 mice provide the possibility for evaluation of medical arms for ARDS with COVID-19.…”
Section: Discussionsupporting
confidence: 91%
“…Antibody-mediated humoral immunity is essential for host defenses, 57 , 58 , 59 while optimal virus clearance in SARS-CoV-2-infected mice also requires CD4 + and CD8 + T cell responses. 60 In this study, we detected significantly lower levels of B cell and T cell responses from DIO mice when compared with lean mice, which may contribute to the increased susceptibility of re-infection in DIO mice.…”
Section: Discussionmentioning
confidence: 99%
“…Zhu et al [ 84 ] evaluated the virus induces a response by interferon (IFN) type I, which promotes the migration of monocytes and macrophages to the lungs the immune response to SARS-CoV-2 in mice. Regarding the innate immune response, the authors noted that SARS-CoV-2 is sensitive to IFN-β, leading to a reduction in viral load.…”
Section: Animal Modelsmentioning
confidence: 99%
“…Regarding the humoral response, immunoglobulins (IgG) specific for the Spike protein (S) of the virus were detected in the blood of mice 21 days after infection. The authors also evaluated the cellular immune response in these animals and observed the presence of different types of T lymphocytes, as well as B lymphocytes and natural killer cells [ 84 ]. In another study, Hassan and colleagues [ 85 ] demonstrated the importance of IFN in the immune response to SARS-Cov-2.…”
Section: Animal Modelsmentioning
confidence: 99%